2020
DOI: 10.1002/stem.3296
|View full text |Cite
|
Sign up to set email alerts
|

Adipose stem cell secretome markedly improves rodent heart and human induced pluripotent stem cell-derived cardiomyocyte recovery from cardioplegic transport solution exposure

Abstract: Heart transplantation is a life-saving therapy for end-stage organ failure. Organ deterioration during transportation limits storage to 4 hours, limiting hearts available. Approaches ameliorating organ damage could increase the number of hearts acceptable for transplantation. Prior studies show that adipose-derived stem/stromal cell secretome (ASC-S) rescues tissues from postischemic damage in vivo. This study tested whether ASC-S preserved the function of mouse hearts and human induced pluripotent stem cell-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…After day 9, media was changed every three days, and beating was observed generally by day 21 of differentiation as stated in previous papers. [ 29–31,48 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After day 9, media was changed every three days, and beating was observed generally by day 21 of differentiation as stated in previous papers. [ 29–31,48 ]…”
Section: Methodsmentioning
confidence: 99%
“…After day 9, media was changed every three days, and beating was observed generally by day 21 of differentiation as stated in previous papers. [29][30][31]48] 2.5. Induced Endothelial Cell (iEC) Differentiation iEC differentiation induction was performed using a previously established protocol.…”
Section: Hipsc Culture and Induced Cardiomyocyte (Icm) Differentiationmentioning
confidence: 99%
“…However, acquiring EVs with high yield and consistent biological activities remains challenging. New technologies, such as microfluidics, are being developed to overcome this impediment (64,65).…”
Section: Secretomementioning
confidence: 99%
“…When streptozotocininduced diabetic mice were transplanted with islets that were previously preserved in the presence of these two AD-MSC secretome fractions, the recipients exhibited better glycemic control (73). Ellis et al reported that functional deterioration of murine heart allografts was mitigated when AD-MSC secretome was added to the cold preservation solution (65). Wang et al showed that miR-199-3p in the heart allograft was depleted during cold preservation, and the level can be recovered when the AD-MSC-derived EVs in the preservation solution transferred miR-199-3p to the graft (74).…”
Section: On the Allotransplantsmentioning
confidence: 99%
See 1 more Smart Citation